Comparison of various morphological types of cementoenamel junction in ground section of permanent tooth - Kundendu Arya Bishen; Himanshu Singh; Sushruth Nayak; Prachi Nayak; Urvashi Tomar; Navneet Agrawal (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of the study was to assess the most common patterns of cementoenamel junction (CEJ) in permanent tooth and most common pattern of CEJ in males and females in permanent tooth. Materials and Methods: A total number of 120 permanent teeth were selected. The ground sections of these teeth were prepared in longitudinal plane. The cementoenamel junction of prepared ground sections was then analyzed and studied. Results: The edge-to-edge pattern of cementoenamel junction was the most common pattern observed, was followed by gap junction, cementum over enamel, and enamel over cementum. In males and females, the most common pattern of CEJ seen was same (edge-to-edge pattern), followed by gap, cementum over enamel, and enamel over cementum. Conclusion: In the present study, out of four patterns of cementoenamel junction, edge-to-edge pattern was the most commonly seen, followed by gap junction, cementum over enamel pattern, and enamel over cementum pattern.